New Ways to Measure Mechanical Losses by Motoring an ICE with Increased Cylinder Pressure - Radek Procházka; Aleš Dittrich; Robert Voženílek; Stanislav Beroun (Applied Sciences, 2022)
The article shows the results of measuring the mechanical losses of a piston engine in two new ways and explains the necessary engine modification for these measurements. At the same time, it compares the results of measuring mechanical losses in the internal combustion engine (ICE) in the current (hitherto exploited) way and in new ways. The first method is not replacing the cylinder charge and regulating the cylinder pressure by feeding compressed air through self-acting valves into the cylinders of the motoring engine. The second method is a closed working cycle by means of an exhaust–intake connection, in which the load pressure in the cylinder is adjusted and maintained by a controlled-intake air supply. With the current method of measuring mechanical losses of a reciprocating internal combustion engine (ICE) by motoring, there are less than half the pressures in the cylinder compared to the pressures during real engine operation (i.e., in the combustion mode). Lower pressures in the cylinder reduce the force load on the piston group and the crank mechanism, and the detected mechanical losses in the engine are thus significantly reduced compared to the reality. In the laboratories of the propulsion units of the Faculty of Mechanical Engineering of the Technical University in Liberec, research is underway on a new method of measuring mechanical losses of a reciprocating internal combustion engine by motoring with charge pressure profiles in engine cylinders comparable to cylinder pressures during standard engine operation. The paper shows the results of measuring the mechanical losses of a piston engine in two new ways and explains the necessary adjustment of the engine for these measurements. At the same time, it compares the results of measuring mechanical losses in a reciprocating engine in the current (hitherto used) way and new ways. The first method is not changing the cylinder charge and regulating the pressure in the cylinder by inserting compressed air through automatic valves into the cylinders of the motoring engine. The second method is a closed working circuit involving connecting the exhaust to the intake, in which the charge pressure in the cylinder is set and maintained by a controlled supply of compressed air to the intake manifold. The first method proved to be a more suitable way to investigate mechanical losses in ICE and determine the dependence of these losses on the pressure conditions in the engine cylinder.